2018
DOI: 10.1158/1078-0432.ccr-18-0323
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 16-Gene Recurrence Score in Patients with Locoregional, High-Risk Renal Cell Carcinoma from a Phase III Trial of Adjuvant Sunitinib

Abstract: Adjuvant sunitinib prolonged disease-free survival (DFS; HR, 0.76) in patients with locoregional high-risk renal cell carcinoma (RCC) in the S-TRAC trial (ClinicalTrials.gov NCT00375674). The 16-gene Recurrence Score (RS) assay was previously developed and validated to estimate risk for disease recurrence in patients with RCC after nephrectomy. This analysis further validated the prognostic value of RS assay in patients from S-TRAC and explored the association of RS results with prediction of sunitinib benefit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…Additionally, a study has reported the validation of a 16-gene recurrence score for RCC using the subjects of the S-TRAC trial 123. This will likely be evaluated in all ongoing trials in which tissue is available for analysis.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…Additionally, a study has reported the validation of a 16-gene recurrence score for RCC using the subjects of the S-TRAC trial 123. This will likely be evaluated in all ongoing trials in which tissue is available for analysis.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…A prospectively designed analysis of immune tissue biomarkers in the S-TRAC trial population reported that a greater CD8 þ T-cell density in tumor tissue was associated with a longer DFS in patients who received sunitinib (24). A validated 16-gene recurrence score (RS) assay, developed to predict the likelihood of recurrence postnephrectomy in patients with locoregional RCC (25), was further validated in a prospectively designed analysis of the S-TRAC population (26). The RS successfully predicted time to recurrence, DFS, and renal cancer-specific survival in both placebo and sunitinib arms (26).…”
Section: Discussionmentioning
confidence: 99%
“…A validated 16-gene recurrence score (RS) assay, developed to predict the likelihood of recurrence postnephrectomy in patients with locoregional RCC (25), was further validated in a prospectively designed analysis of the S-TRAC population (26). The RS successfully predicted time to recurrence, DFS, and renal cancer-specific survival in both placebo and sunitinib arms (26). In addition, a pharmacogenomic analysis of the S-TRAC trial found that SNPs in the VEGFR1 and VEGFR2 genes were associated with longer DFS in patients receiving adjuvant sunitinib (27).…”
Section: Discussionmentioning
confidence: 99%
“…Better selection of patients to establish a more accurate knowledge of risk has been approached by tumor and stroma signature, including a 34‐gene subtype predictor to classify clear cell renal carcinoma tumours according to ccA (good risk) and ccB (poor risk) subtypes, and a 16‐gene assay for calculating a recurrence score to predict recurrence after surgery, but are not part of ongoing trials.…”
Section: Future Prospectsmentioning
confidence: 99%